2019
DOI: 10.1016/j.oceaneng.2019.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase flow induced vibrations in a marine riser conveying a fluid with rectangular pulse train mass

Abstract: A riser conveys fluids from a subsea system to a host floater; however, oil and gas phases may alternate, increasing pipe's stress and damaging downstream facilities. This paper studies the nonlinear planar vibrations of a steel lazy wave riser excited by slug flow. The employed formulations comprise the Euler-Bernoulli beam model and the steady plug-flow model with a time-space-varying mass per unit length in the form of a rectangular pulse train. The equations are solved by a Runge-Kutta finite difference sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 67 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…An experiment performed by Zhu et al is utilized to evaluate the efficacy of the ALE-ANCF simulation program. 22 Table 1 presents the main parameters of the flexible riser model. It should be noted that the values of superficial velocity and slug flow length in Table 1 are estimated approximations, derived from the volumetric flow rates of the liquid and gas.…”
Section: Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…An experiment performed by Zhu et al is utilized to evaluate the efficacy of the ALE-ANCF simulation program. 22 Table 1 presents the main parameters of the flexible riser model. It should be noted that the values of superficial velocity and slug flow length in Table 1 are estimated approximations, derived from the volumetric flow rates of the liquid and gas.…”
Section: Model Validationmentioning
confidence: 99%
“…An experiment performed by Zhu et al. is utilized to evaluate the efficacy of the ALE‐ANCF simulation program 22 . Table 1 presents the main parameters of the flexible riser model.…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the increased internal flow speed can increase the amplitude, but the vibration frequency can decrease. Cabrera-Miranda and Paik [18] used the Euler-Bernoulli beam model and the plug-flow model for the pipe structure and the internal fluid of the riser, respectively. The study utilized the finitedifference method, to solve for the spatial domain, and the Rung-Kutta for the temporal part to reveal the dynamics of the internal flow.…”
Section: Introductionmentioning
confidence: 99%
“…In offshore engineering, more and more research results have emerged 1‐3 . A marine riser is one of the most typical systems and can be used as a curved pipe to convey fluid oil to the seabed 4 . Driven by engineering application, flexible material has the advantage of light weight, low energy consumption and fast speed, which are widely used in modern offshore engineering.…”
Section: Introductionmentioning
confidence: 99%